Title: Literature review of Supplier Development Activities and Performance Activities with Hypothesis to Identify Relationship (International Journal of Food and Nutritional Sciences, 2022)
Purpose of this paper is to review the supplier development activities (SDAs) and itsPerformance outcomes (POs), categorization of these SDAs and POs and also setting thehypothesis to identify the relationship amongst them. Through an extensive literature review of67 papers from various academic databases 28 SDAs and 33POs are identified for this study.These 28 SDAs are categorized into five different categories and 22 POs into three categories inconsultation with the industry practitioners. The SDAs five categories are strategic efforts (SE),Knowledge and information sharing (KIS), Investment (INV), Working together with suppliers(WTS), Involvement of buyer in supplier activities (IBS) and POs are also categorized into threecategories i.e. supplier performance improvement (SPI), buyer’s competitive advantageimprovement (BCAI) and buyer-supplier relationship improvement (BSRI). In total 13hypothesis were set to identify the interrelationship amongst SDAs and POs. This study can befurther extended to check this proposed hypothesis by using structural equation modeling orregression analysis.